Sobrevivência ambulante no espaço urbano: informalidade e trabalho na Feira José Avelino, em Fortaleza-Ceará - Alves, Marco Aurélio de Andrade (2020)
While a part of the city of Fortaleza falls asleep, the José Avelino Clothing Fair awakens in an explosive pulse, pumping the heart of the City Center in an agitated movement of people coming from different states of Brazil, composing an urban scenario of intense dynamism and heterogeneity. The José Avelino Fair or the Dawn Market (Feira da Madrugada), as it is also known, represents a ‘breadwinning’ space for thousands of street vendors who sell clothing. Furthermore, the Fair is also depicted amid ‘controversy’ by the news and the local media as a ‘source of problem’ for the city, as it constitutes an image and representation of a 'disordered' space for urban management. In 2017, within the scope of a Requalification Policy for the City Center of Fortaleza, the José Avelino Fair was removed, with the establishment of the private enterprise Centro Fashion, which received a significant part of the vendors. The Fair however resists, and now no longer with stalls, but with street shopping, in much more precarious conditions. In its different times and configurations and, especially, as the locus of informal work, this Fair instigated my curiosity as a researcher of urban space. Thus, this thesis embodies analyses and reflections developed between the years 2015 to 2019, with the main focus on the issue of informal work at the José Avelino Clothing Fair, discussing the process of precarization which permeate the working activities of vendors. In the expository dynamics of the dissertation, I present results of a research comprising of extensive fieldwork, in which dialogues, images, paths and diverse impressions about a complex informal popular market, created in the meshes of the city, are made explicit. The text is structured in eight sections, including Introduction, Methodological Pathways of Research and Final Remarks, presenting five sections that represent major thematic axes: The Fair and the City; Informality in the Urban Space and Requalification Policy; City and Work; Precarious Work and Informality; Trajectories of Work and Life. Entering José Avelino’s complex world required methodological creativity, given the changing and extremely dynamic nature of the field itself. In this sense, the city, which at times seems quite familiar, ended up demanding from the researcher, greater capacity for ‘making the familiar strange’. The initial visits to the field made it possible for me to realize the expansive and 'stubborn' character that the Fair had acquired. Its expansions and stretches revealed different logics of ‘appropriation of public space’ by informal workers. Throughout the dialogues with the subjects of the Fair, I noticed, in their discourse, the existence of a tension and at the same time a constant uncertainty regarding the ‘irregular’ situation of remaining in the street market, stimulated, mainly, by the frequent threats of removal from urban space. In order to capture and apprehend both the objective and subjective factors of precariousness in the work of informal workers at José Avelino Fair, I made a detailed and thick description of the daily movement of these vendors at different times and spaces. To this end, I opted for the practice of participant observation as a way of perceiving daily life beyond what was established, paying attention to the different ways in which vendors take ownership of the space and the extent to which their practices come up against the determinations of the public sector. At the same time, I was able to apprehend how these conflicting relationships further intensify the worker’s condition of instability, marking a specific type of precarious work. In order to unveil this empirical reality, I carried out bibliographic research, contemplating categories that are central for the object. To capture the kaleidoscope of situations constituting the Fair, I made use of records in a field journal, also using the support of a photo camera. The various notes and records of these diaries were inserted here and are constantly in dialogue with the theories and speeches of the various subjects that make up the José Avelino Fair. I conducted research in newspapers and surveyed files of legislation that regulate street commerce in the City of Fortaleza. To capture the senses and meanings nourished by workers in their daily lives, I conducted 35 semi-structured interviews that pointed out fundamental aspects for understanding informality and the job insecurity processes in which segments of the José Avelino Fair workers are inserted. Finally, the investigative paths, articulated in their multiplicity, allowed me to access narratives and meanings throughout the research process.